2019
DOI: 10.1108/ijchm-10-2018-0805
|View full text |Cite
|
Sign up to set email alerts
|

Does the hospitality industry need or deserve talent?

Abstract: Purpose This paper aims to confront the most challenging issues that the hospitality industry faces. This relates to the recruitment and retention of talented future leaders. This is a long-standing issue but one that is increasing in importance as industry changes, combined with external pressures within the labour market (demographic and competitive), act to restructure the recruitment landscape in many countries. Design/methodology/approach This paper provides a literature-based analysis that addresses tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 69 publications
0
56
0
Order By: Relevance
“…The current paper shows that a negative event, like COVID-19, that impacts an industry harder than others, can relate to negative attitudes and behaviors toward the industry. This is particularly important considering that industries, like the hospitality industry, often rely on a pipeline of employees to maintain an effective workforce (Baum, 2019;Whysall et al, 2019). Both the qualitative (Study 1) and quantitative (Study 2) data revealed that the pandemic has made employees question their decision to work in the hospitality industry.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The current paper shows that a negative event, like COVID-19, that impacts an industry harder than others, can relate to negative attitudes and behaviors toward the industry. This is particularly important considering that industries, like the hospitality industry, often rely on a pipeline of employees to maintain an effective workforce (Baum, 2019;Whysall et al, 2019). Both the qualitative (Study 1) and quantitative (Study 2) data revealed that the pandemic has made employees question their decision to work in the hospitality industry.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…While the hospitality industry provides a vast number of jobs, the characteristics of the industry stimulate a unique demand for hospitality education and programs. The hospitality industry calls for employees fluent in their operational knowledge and ability to integrate new technology and trends as well as the interpersonal skills necessary to meet the changing and growing demands of customers and customer service (Baum, 2019;Brown et al, 2015). Therefore, the hospitality industry has established a cooperative and mutually beneficial relationship with hospitality university programs and majors where the industry creates a need for talent and skills, and university programs provide talented individuals (Baum, 2019).…”
Section: Hospitality Industry As a Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the above, future research may investigate the role of online leisure crafting in these outcomes to further extend our model. (Baum, 2019). It could be valuable to investigate how leadership may play a role in our model to provide additional theoretical implications and practical implications for the hospitality industry.…”
Section: Limitations and Future Researchmentioning
confidence: 99%